Partial factors for loads due to special vehicles on road bridges. (1st January 2016) - Lenner, Roman; Sýkora, Miroslav
Highlights: Considering special heavy vehicles on bridges according to design provisions is problematic. Methodology for calibrating partial factors for special vehicles is proposed. Stochastic models, sensitivity factors and target reliability are discussed. The commonly accepted partial factor of 1.35 can be significantly reduced. Abstract: The structural standards for bridge design are well calibrated to account for the general traffic loading and expected use of the structure. Consideration of special heavy vehicles on bridges is often regarded according to provisions for the general traffic model in standards that may be, however, inconsistent and problematic due to a number of reasons. This contribution identifies the characteristics of special vehicles and proposes the methodology for calibration of the related partial factors. Key steps of the methodology consist of assessing static load effect, dynamic amplification, model uncertainty, sensitivity factors and target reliability. Careful consideration of these influences then yields partial factors that correspond to the definition of special loading and can be modified to distinguish between design and assessment situations. It appears that the commonly accepted partial factor of 1.35 may be reduced for an increased ratio of permanent- to traffic loads, decreased target reliability and for controlled speed of the vehicle and/or its position on a bridge. When multiple crossings of the same vehicle or vehicles of the same type during a reference period are considered, it is proposed to keep the partial factor independent of the number of crossings while the characteristic value should be adjusted with respect to the expected number of crossings.